Family Mobilization With Stunting Case Toward Children Under Five Years Old In Indonesia: Literature Review - Talapessy, Elsa Yolanda; Susanto, Tantut; Susumaningrum, Latifa Aini; Septiyono, Eka Afdi (Journal of Rural Community Nursing Practice, 2023)
Stunting is the inadequacy of nutritional intake from the womb to the child at the age of five, which is indicated by the child having less length or height comparing to the age. In this study, the researcher linked family mobility as one of the factors causing the increasing case of stunting. The purpose of this literature study is to describe family mobilization with the stunting case in children under five in Indonesia. The research design used in this study was a traditional literature review. Articles are tracked using several search engines (Google Scholar, PubMed, Springer link, Sinta, and Plos One). The results of this study indicated that family mobilization in reaching health services can affect the nutritional status of children under five. The affordability of health services is caused by several factors such as road access, distance and travel time. It also relates to the family residence, the pattern of care provided, and the socio-economic status of the family which can cause children under five experiencing stunting. The conclusion in this study is that family mobilization such as a lack of family health attention in reaching health services, inadequate needs and a healthier lifestyle or low economic status, as well as a poor or lack parenting knowledge can cause children under five susceptible to infectious diseases so that the children are prone to stunting.